Membangun Literasi Kimia Kritis: Kajian Literatur Sistematis - Munawwarah, Munawwarah; Alqadri, Zulqifli (STKIP HARAPAN BIMA, 2025)
This study aims to map the development of chemical literacy in chemistry education and to identify future research directions toward Critical Chemical Literacy through a systematic literature review. The study employed a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. From 100 open-access articles identified between 2015 and 2024, fifty passed the screening stage, and twenty met the inclusion criteria for analysis. Data were extracted based on metadata (year, educational level, topic, and research design), instructional strategies, chemical literacy assessment instruments, and reported findings. Descriptive and thematic analyses were conducted to identify trends, key results, and research gaps. The findings reveal that chemical literacy research remains concentrated in upper-secondary education, mainly focusing on acids–bases, equilibrium, and reaction rates. The most frequently applied instructional strategies are Context-Based Learning (CBL) and Socio-Scientific Issues (SSI), followed by PBL/STEAM, inquiry, argumentation, and ethnoscience integration. Assessment instruments such as A-BCLT, CELT, and IA-ATCL have been developed but still emphasize cognitive aspects over affective, social, and critical agency dimensions. The review concludes that future chemical literacy research should expand across educational levels, diversify investigated topics, and integrate digital technologies and global issues such as sustainability and climate change. Practically, the findings encourage teachers and policymakers to design curricula and assessments that position chemical literacy as a strategic 21st-century competence.